The Production Efficiency of Small Medium Enterprises in West Sumatera Province - Nurul Agustin; Alpon Satrianto (Department of Development Economics, Universitas Sriwijaya, 2023)
The purpose of this study is to determine the effect of capital, labor, and resources on the technical efficiency production of SMEs in West Sumatra and to see whether the SMEs production in West Sumatra is technically efficient. The type of data used in this study is panel data for 19 regencies/cities in West Sumatra from 2015 to 2021 using the Stochastic Frontier Analysis (SFA) approach. This research examines production efficiency technically at SMEs in the West Sumatra region. The result of this study indicates that the production factors of capital and resources have a positive and significant effect on the production of SMEs in West Sumatra, while labor has a negative and insignificant effect on the production of SMEs in West Sumatra. The result of the technical efficiency calculation shows that the mean level of technical efficiency of the SMEs production in West Sumatra from 2015 to 2021 is 0.543 or 54.3 percent, which means that production in SMEs is technically inefficient. This research implies that the government can compile regulations and road maps that can increase the productivity of SMEs in the West Sumatra region, and for SMEs to be able to engage more broadly with sustainable programs for production efficiency such as attending training and business guidance, using the rural business credit program from the government, as well as establishing cooperation partners for raw materials with other SMEs.